Effect of the Elementary Stuff and Type of Utensils Used on Rate of Power Consumption in Microwave Ovens - Ali, Adnan Mohmoud (Al-Mukhtar Journal of Sciences, 2002)
This research work discusses the effect of the elementary stuff composing the food, on the quantity of electrical power needed to cooking in microwave ovens, like fats, the water content and elementary salt. Studying the effect of frozen elementary stuff, type of utensils used, and metallic or glass ones, on quantity of electrical power consumed.